The Determinants of Network Capability and Born Global Performance, Insight from SMEs In Emerging Country - Yakuttinah, Marjan; Fenitra, Rakotoarisoa Mamirina (RSF Conference Series: Business, Management and Social Sciences, 2023)
In recent year, the new digital era provides a wider opportunity to tap the worldwide market, facilitate trade, and ease the transaction process without borders. However, companies need to acknowledge and be able to seize these opportunities in entering the global market. This work examines the influence of entrepreneur orientation, Cultural intelligence, and social capability on network capability. Besides, this work further extends to investigate the impact of network capability on born global performance. The Dynamic Capability Theory was used as a foundation of the present conceptual framework. This study surveyed 75 born global firms, the sample of this study consist of 300 employees and founders. The Structural equation Modelling found that entrepreneur orientation, cultural intelligence, and social capital are important factors that have a positive influence on network capability. Besides, the findings found that network capability foster born global performance. The findings can be used as a guide for startups and entrepreneurs to explore global opportunities and give a competitive advantage in exploring foreign markets. Furthermore, this work provides a significant contribution to the literature and the limitation of the study set a venue for future research agenda.